Histological sub‐classification of cirrhosis using collagen proportionate area in patients with chronic hepatitis C. (7th May 2021) - Papatheodoridi, Margarita; Hall, Andrew R.; Rodríguez‐Perálvarez, Manuel; Pieri, Giulia; Germani, Giacomo; Gale, Jeremy D.; Burgess, Gary C.; Pinzani, Massimo; Dhillon, Amar P.; Tsochatzis, Emmanuel A.
Abstract: Collagen proportionate area (CPA, %) is used to quantify liver fibrosis. Here, we assessed CPA performance to sub‐classify cirrhosis. CPA was measured in explanted livers from consecutively transplanted patients for hepatitis C virus‐related cirrhosis. Model for end‐stage liver disease (MELD), Child‐Pugh score and decompensating events (ascites, variceal bleeding, non‐obstructive jaundice and encephalopathy) were recorded at the time of liver transplant. Of the 154 patients, 24%, 12%, 35%, 24% and 5% had zero, one, two, three and four previous decompensating events. Patients with decompensation had significantly higher CPA than those without (25.1 ± 8.4 vs 15.8 ± 5.5, P  < .001). Decompensation was independently associated with CPA, bilirubin and albumin or with CPA and MELD score. CPA did not differ between patients with one, two, three or four decompensating events (22.2 ± 6.3 vs 26.6 ± 8.9 vs 24.5 ± 7.7 vs 24.4 ± 10.9, P  = .242). Overall, CPA correlates with the clinical severity of cirrhosis until the advent of decompensation but not with subsequent decompensating events.